2017
DOI: 10.1038/ncomms15592
|View full text |Cite
|
Sign up to set email alerts
|

Pyk2 modulates hippocampal excitatory synapses and contributes to cognitive deficits in a Huntington’s disease model

Abstract: The structure and function of spines and excitatory synapses are under the dynamic control of multiple signalling networks. Although tyrosine phosphorylation is involved, its regulation and importance are not well understood. Here we study the role of Pyk2, a non-receptor calcium-dependent protein-tyrosine kinase highly expressed in the hippocampus. Hippocampal-related learning and CA1 long-term potentiation are severely impaired in Pyk2-deficient mice and are associated with alterations in NMDA receptors, PSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
143
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(159 citation statements)
references
References 70 publications
16
143
0
Order By: Relevance
“…In the hippocampus of Pyk2 -/mice, we previously observed decreased levels of several synaptic proteins [15]. In the striatum, neither GluN2A nor PSD-95 levels were altered in Pyk2 -/mice (Figures 1C and D).…”
Section: Pyk2 Deletion Does Not Alter Striatal Proteinsmentioning
confidence: 70%
See 2 more Smart Citations
“…In the hippocampus of Pyk2 -/mice, we previously observed decreased levels of several synaptic proteins [15]. In the striatum, neither GluN2A nor PSD-95 levels were altered in Pyk2 -/mice (Figures 1C and D).…”
Section: Pyk2 Deletion Does Not Alter Striatal Proteinsmentioning
confidence: 70%
“…Pyk2 is a Ca 2+ -dependent non-receptor tyrosine kinase highly expressed in forebrain neurons [9] where it is activated by neuronal activity and excitatory neurotransmission [10][11][12]. Pyk2 can associate with the NMDA receptor complex and has a role in synaptic plasticity [11,[13][14][15]. Ca 2+ triggers Pyk2 autophosphorylation on Tyr-402, which recruits and activates Src-family kinases (SFKs) [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 In contrast, Pyk2 is enriched in the postsynaptic density of neurons and serves to tune synaptic plasticity and regulate neuronal differentiation and migration in the CNS. [14][15][16][17][18][19][20] Pyk2 signaling is also involved in bone remodeling and leukocyte motility. 3,21 Canonical FAK activation involves recruitment to membrane focal adhesions via interactions with paxillin, talin, and vinculin at clustered integrins.…”
Section: Introductionmentioning
confidence: 99%
“…Pyk2 is a non-receptor tyrosine kinase and is very abundantly expressed in the hippocampus of postnatal rats, reaching maximal levels in adulthood [16]. We and others recently found that Pyk2 plays important roles in dendritic and spine morphogenesis [7,17,18]. Pyk2 is post-synaptic located and interacts with NMDA receptors [19] or PSD95 [20], implicating a role of Pyk2 in both LTP [21,22] and LTD [23].…”
Section: Introductionmentioning
confidence: 99%